Online threats and risky behaviour from the perspective of Malaysian youths - Waheed, Moniza (Taylor's University, 2019)
The usage of the internet has become inevitable in this day and age. While there are many benefits that come with its usage, there is also a lot of harm, particularly for adolescents. While there are ample studies proving this, there are no known studies which explain the indulgence of online risky behaviour from the perspective of the youth. Therefore, the main aim of this study is to understand the issue of online threats from the Malaysian youths’ perspective. Findings from four focus group discussions consisting of 32 adolescents from urban and rural secondary schools in Malaysia show that despite displaying an understanding of the meaning of online threats, adoslescents still indulge in risky behaviour online. They are found to treat the online space as a socializing platform where social prestige is sought. Additionally, some youths from the rural area are found to be victims of cyberbullying, while some from the urban area are the culprits who commit the act. Findings also show that “befriending strangers online” and “cyberbullying” are hot topics discussed among the youth. Hence, these topic areas should receive sufficient attention in future policymaking and practices undertaken by the relevant agencies in Malaysia.